2019
DOI: 10.1017/s1755773919000043
|View full text |Cite
|
Sign up to set email alerts
|

How well are citizens represented by their governments? Issue congruence and inequality in Europe

Abstract: This study analyses congruence across various issues in 16 European democracies. Making use of public opinion and expert survey data, our analyses show that congruence between the policy preferences of citizens and the stances of governments is much more complex than what is revealed by studies focusing on ideology solely. Size and directions of incongruence are larger and more systematic on specific issues than on the left–right scale. On redistribution, citizens are more to the left than their governments, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 61 publications
2
28
0
6
Order By: Relevance
“…Such political inequalities seem to extend to the important area of substantive representation (Pitkin 1967: 112–143). Studies in various European countries show that party positions are more congruent with the views of higher educated citizens than the views of those with lower levels of education (Lesschaeve 2016; Aaldering 2017; Rosset & Stecker 2019). However, despite the disproportionate presence of the higher educated throughout the political process, there is no direct evidence that highly educated citizens have a larger influence on government policy.…”
Section: Frameworkmentioning
confidence: 99%
“…Such political inequalities seem to extend to the important area of substantive representation (Pitkin 1967: 112–143). Studies in various European countries show that party positions are more congruent with the views of higher educated citizens than the views of those with lower levels of education (Lesschaeve 2016; Aaldering 2017; Rosset & Stecker 2019). However, despite the disproportionate presence of the higher educated throughout the political process, there is no direct evidence that highly educated citizens have a larger influence on government policy.…”
Section: Frameworkmentioning
confidence: 99%
“…Earlier work has found that, in general, the quality of representation is better in terms of left vs right ideological preferences, i.e., the main dimension of conflict in European politics, but worse in terms of cultural and European integration dimensions (Costello et al, 2012). National-level research on representation and congru-ence is moving towards the study of single-issue dimensions (see, for example, Rasmussen, Reher, & Toshkov, 2019;Stecker & Tausendpfund, 2016) and some first attempts have been made to study unequal representation across issue-dimensions (e.g., Rosset & Stecker, 2019). Future work on EU-level representation should thus also go beyond the general left-right dimension to examine the EU institutions' congruence with income groups on key policy issues of concern, such as European integration, immigration, and redistribution.…”
Section: Discussionmentioning
confidence: 99%
“…Among democracies, it would be interesting to investigate whether the variation in policy responsiveness to different social groups explains the variation in their revolutionary attitudes. For instance, research has shown that in most democratic countries, policies are more responsive to the preferences of rich and educated people (Bovens and Wille, 2017; Gilens, 2005; Rosset and Stecker, 2019), something explaining their lower revolutionary attitudes.…”
Section: Discussionmentioning
confidence: 99%